Role of molecular markers in identifying genetic disorders - Assiri, Khaled Ali; Alrasis, Mohammed Saleh; Mashlawi, Ahmed Ibrahim; Alayda, Maha Hail; Aljndbai, Ahmed Mohammed (International Journal Of Community Medicine And Public Health, 2024)
Molecular markers are critical tools in identifying genetic disorders, allowing for precise diagnosis, risk assessment, and personalized treatment approaches. They are classified into various categories, including single nucleotide polymorphisms (SNPs), short tandem repeats (STRs), and restriction fragment length polymorphisms (RFLPs), each serving distinct roles in genetic diagnostics. SNPs are widely used in genome-wide association studies (GWAS) to identify genetic predispositions to complex diseases, while STRs are valuable in diagnosing disorders like Huntington’s disease. RFLPs, though less commonly used today, remain important in specific diagnostic contexts. The application of molecular markers spans a wide range of genetic disorders, from monogenic conditions such as cystic fibrosis (CF) to complex diseases like hereditary breast and ovarian cancer syndrome and fragile X syndrome. These markers enable early detection and targeted interventions, improving patient outcomes. However, several challenges hinder their widespread adoption, including difficulties in interpreting genetic data, limited access to genetic screening, and ethical concerns related to privacy and genetic discrimination. Future directions in the use of molecular markers for genetic screening involve integrating advanced technologies like next-generation sequencing and combining molecular data with other omics approaches to provide a more comprehensive understanding of genetic disorders. Addressing the challenges of data interpretation, accessibility, and ethical issues will be crucial in expanding the utility of molecular markers in clinical practice. The advancements in molecular marker technology and their applications in detecting specific genetic disorders hold promise for improving diagnostic accuracy and personalized treatment strategies. However, ensuring that these technologies are accessible and ethically implemented will be key to their success in transforming healthcare. The ongoing evolution of molecular markers and genetic screening technologies suggests a future where early diagnosis and personalized medicine become standard care for genetic disorders.